Design and fabrication of cylinder head turn table (rotate 360 degree) - Addam, Annuar (2007)
This project is mainly concerned on designing and fabricating the cylinder Head Turn Table (360 degree) that can be used to hold the cylinder head for easy repair. The main objective in this project is to give an experience and knowledge for student to make the project and activity successfully. This table is the first project for this university and suitable as an application to hold the cylinder head in Faculty of Mechanical (FKM) Lab in automotive section. This project involves the process of designing the table by considering the shape, functionality, portability and the manufacturing cots for people to use it. The material used is easy to gain, because it only using rectangular hollow steel and round steel hollow. So that the method joining that can be compatible in assembled this table is welding processes. In assembled the wheel, fastening method is the best chosen because it's only use bolt and nut to bind the wheel with the base ofthis table. After all the process had been done, this table may help us to understand the fabrication and designing process that involved in this project.